Improved Weighted Restriction Estimates in R3 - Shayya, Bassam (The Journal of geometric analysis, 2023)
Suppose 0 < α ≤ n , H : R n → [ 0 , 1 ] is a Lebesgue measurable function, and A α ( H ) is the infimum of all numbers C for which the inequality ∫ B H ( x ) d x ≤ C R α holds for all balls B ⊂ R n of radius R ≥ 1 . After Guth introduced polynomial partitioning to Fourier restriction theory, weighted restriction estimates of the form ‖ E f ‖ L p ( B , H d x ) ≲ R ϵ A α ( H ) 1 / p ‖ f ‖ L q ( σ ) have been studied and proved in several papers, leading to new results about the decay properties of spherical means of Fourier transforms of measures and, in some cases, to progress on Falconer’s distance set conjecture in geometric measure theory. This paper improves on the known estimates when E is the extension operator associated with the unit paraboloid P ⊂ R 3 , reaching the full possible range of p , q exponents (up to the sharp line) for p ≥ 3 + ( α - 2 ) / ( α + 1 ) and 2 < α ≤ 3 .